Nanoparticle-Based FM-MCF LSPR Biosensor With Open Air-Hole - Yang, Chuanhao; Xiao, Shiyan; Wang, Qi; Zhang, Hongxia; Yu, Hui; Jia, Dagong (Frontiers in Sensors, 2021)
A nanoparticle-based few-mode multi-core fiber (FM-MCF) localized surface plasmon resonance (LSPR) biosensor is proposed and analyzed using the finite element method (FEM). With the aid of open air holes, the gold nanoparticles are easily assembled on the surface of this FM-MCF LSPR biosensor. Through multiple investigations, the performance of the sensor can be improved by properly setting gold nanoparticle configurations, such as radius, positions, shapes, and nanoparticle arrays. The simulation results show that when three circular gold nanoparticles with a radius of 150 nm are placed symmetrically in the open air hole and the angle between adjacent nanoparticles is 5°, the maximum sensitivity of 7351.6 nm/RIU (LP02y mode na = 1.38) can be obtained in the sensing range of 1.33-1.38, which covers the refractive index (RI) of biological fluids, such as bovine serum albumin (BSA) solution and human Immunoglobulin G.